Tapered inner-cladding fiber design for uniform heat deposition in Ytterbium-doped fiber amplifiers. (26th February 2015) - Huang, Zhihua; Zhang, Yongliang; Deng, Ying; Lin, Honghuan; Li, Qi; Zhao, Lei; Wang, Jianjun
Abstract: A method for designing double-clad fiber with tapered inner cladding and uniform core is proposed for linear pump power profile, i.e. uniform heat deposition, in the ytterbium-doped fiber amplifier. The analytical formula for the inner-cladding diameter profile along the fiber is given. The inner-cladding diameter near the pump injection port is determined purely by the diameter of the doped region, the number density of the doped ions, the absorption cross section at the pump wavelength and the length of the fiber. The simplified linearly varying inner-cladding diameter is proven to have a smoother heat deposition profile with lower maximum thermal load in both the co-pumping scheme and the counter-pumping scheme.